The Impact of Halal Tourism on the Economy of Communities Around Tourism Objects - Reza Abdilla Sandy; Mohd Iqbal Abdul Muin (Universitas Islam Negeri Alauddin Makassar, 2023)
Halal tourism as a tourism concept according to Islamic sharia which offers religious facilities that attract tourists. Halal tourism has the potential to increase economic growth. This study uses a quantitative approach. The sampling technique used nonprobability sampling with a sample of 30 respondents. The results of the study show that halal tourism has a significant effect on the economy in the community around the Lotus Lake tourist attraction, Tinggi Raja Village, Asahan Regency. Based on an Islamic perspective, the impact of halal tourism on the economy can be seen from economic activity by trading and the community also getting halal jobs. Tourist destinations have also provided facilities according to Islamic law, such as Qibla directions at inns, information on the nearest mosque, places of worship for tourists and Muslim employees, paying attention to halal living with the availability of halal food and drinks provided at tourist spots, separate ablution areas for men and women, supporting facilities for performing prayers, and separate places for men and women and making it easier to purify.